2018
DOI: 10.5194/acp-18-6171-2018
|View full text |Cite
|
Sign up to set email alerts
|

Secondary organic aerosol production from pinanediol, a semi-volatile surrogate for first-generation oxidation products of monoterpenes

Abstract: Abstract. We have investigated the production of secondary organic aerosol (SOA) from pinanediol (PD), a precursor chosen as a semi-volatile surrogate for first-generation oxidation products of monoterpenes. Observations at the CLOUD facility at CERN have shown that oxidation of organic compounds such as PD can be an important contributor to newparticle formation. Here we focus on SOA mass yields and chemical composition from PD photo-oxidation in the CMU smog chamber. To determine the SOA mass yields from thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
(70 reference statements)
1
8
0
Order By: Relevance
“…However, experimentally derived volatilities from desorption thermograms measured with a FIGAERO (Filter Inlet for Gases and AEROsols) show a good agreement with the combination of semiempirical methods and theoretical model calculations (Lopez-Hilfiker et al, 2014;Schobesberger et al, 2018). This was recently verified in a complementary study of the α-pinene ozonolysis products examined here (Ye et al, 2019), in which the volatility distribution of molecules in the nucleated particles, measured with a FIGAERO inlet over a wide range of temperatures, is in good agreement with those estimated by Stolzenburg et al (2018).…”
Section: Volatility Basis Set Modelsupporting
confidence: 75%
See 2 more Smart Citations
“…However, experimentally derived volatilities from desorption thermograms measured with a FIGAERO (Filter Inlet for Gases and AEROsols) show a good agreement with the combination of semiempirical methods and theoretical model calculations (Lopez-Hilfiker et al, 2014;Schobesberger et al, 2018). This was recently verified in a complementary study of the α-pinene ozonolysis products examined here (Ye et al, 2019), in which the volatility distribution of molecules in the nucleated particles, measured with a FIGAERO inlet over a wide range of temperatures, is in good agreement with those estimated by Stolzenburg et al (2018).…”
Section: Volatility Basis Set Modelsupporting
confidence: 75%
“…be observed as temperature decreases. This decrease in O/C ratio with decreasing temperature was also observed in the particle phase by Kristensen et al (2017) and Ye et al (2019) and raises the question of the extent to which the reduction in oxidation also affects NPF.…”
Section: Effect Of Temperature On α-Pinene Oxidation and Hom Formationmentioning
confidence: 61%
See 1 more Smart Citation
“…Third, the large majority of organic oxidation products are likely to be oxygenated species with lower vapor pressure than the precursors that remain in the gas phase (traditional SVOCs). Later-generation chemistry of these products remains an important topic that cannot be forgotten (Donahue et al, 2005(Donahue et al, , 2012a; these subsequent steps have already been shown to be efficient sources of HOMs (Schobesberger et al, 2013;Ye et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Third, the large majority of organic oxidation products are likely to be oxygenated species with lower vapor pressure than the precursor that remain in the gas phase ("traditional" SVOCs). Later-generation chemistry of these products remains an 5 important topic that can not be forgotten (Donahue et al, 2005(Donahue et al, , 2012a; these subsequent steps have already been shown to themselves be efficient sources of HOMs (Schobesberger et al, 2013;Ye et al, 2018).…”
mentioning
confidence: 99%